Perancangan Panti Rehabilitasi Ketergantungan Narkoba Dengan Tema Arsitektur Perilaku - Firda Utami; Suprayitno Suprayitno; Rina Saraswaty (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
Abuse of narcotics, trafficking illegal drugs becomes a matter of great concern. The issue is already threatening the lives of the next generation of the nation, even a global problem that has become a serious threat in the life of nation and state, not least in Indonesia. Drugs rehabilitation center is a place to rehabilitate people who use drugs. Moreover, drugs rehabilitation center is a place to stop drug user dependency. Based on the problem designing, there are some summaries as follows: (1) Site design of a drugs rehabilitation center are designed to get a nice views and in accordance with the function. (2) Mass organizations are designed to be easily accessible and make the buildings get enough sunshines. (3) Drugs patient has to follow rehabilitation steps from isolation rooms in medical rehabilitation units to reduce drug dependence and interact with society.